2021
DOI: 10.1186/s12891-021-04028-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of subgroup effect with an individual participant data meta-analysis of randomised controlled trials of three different types of therapist-delivered care in low back pain

Abstract: Background Proven treatments for low back pain, at best, only provide modest overall benefits. Matching people to treatments that are likely to be most effective for them may improve clinical outcomes and makes better use of health care resources. Methods We conducted an individual participant data meta-analysis of randomised controlled trials of three types of therapist delivered interventions for low back pain (active physical, passive physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…While many suggested possible interventions for Clusters 2 and 3 are psychological in nature recent research suggests those with higher disability levels may show greater improvements from such interventions . 82…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many suggested possible interventions for Clusters 2 and 3 are psychological in nature recent research suggests those with higher disability levels may show greater improvements from such interventions . 82…”
Section: Discussionmentioning
confidence: 99%
“…While many suggested possible interventions for Clusters 2 and 3 are psychological in nature recent research suggests those with higher disability levels may show greater improvements from such interventions. 82 Multiple comparisons in this study increase the possibility of type I error. 83 However, as LCA is an exploratory technique for determining the existence of clusters, 77 when profiling derived clusters it may be more appropriate to maintain p-values such that there may be a greater chance of a type I error but less chance of a type II error.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…One systematic review that included larger randomised controlled trials (RCT) found the following potential treatment moderators in LBP interventions on disability and pain (high evidence): age, employment status, back pain status, medication use, treatment expectations and educational level 90 . All factors, except treatment expectations, have been confirmatory tested 91,92 in metaanalyses of individual participant data 93 . However, they failed to reach clinically meaningful levels of effect modification of different therapist delivered interventions compared to non-active usual care 91 , or of manipulative treatment compared to other treatments 92 .…”
Section: Treatment Moderatorsmentioning
confidence: 98%
“…All factors, except treatment expectations, have been confirmatory tested 91,92 in metaanalyses of individual participant data 93 . However, they failed to reach clinically meaningful levels of effect modification of different therapist delivered interventions compared to non-active usual care 91 , or of manipulative treatment compared to other treatments 92 . Identifying and confirming factors moderating the treatment effects is challenging due to inconsistent availability of participant characteristics, heterogeneity in treatments, and insufficient power to plausibly show an interaction effect [90][91][92] .…”
Section: Treatment Moderatorsmentioning
confidence: 98%
“…4 Stratification using a screening tool, clinical judgement or according to baseline patient reported outcomes, could reduce the burden of disability and assist with delivery of the right care at the right time. 5,6 Recent guidance issued by NICE 7 found insufficient evidence to indicate whether any psychological, biological or social factors are predictive of successful outcomes in pain management and further research into barriers to successful pain management were recommended. 7 The potential for high risk of bias, in the current evidence base was highlighted due to exclusion of people in studies with particular psychological prognostic features.…”
Section: Introductionmentioning
confidence: 99%